Virtual realization and geometric discriminant algorithm of the industrial robot end-effector's position and orientation. (17th February 2018) - Ma, Fei; Jia, Rui-Qing
Abstract: Based on geometric characteristics of a typical six DOF industrial robot with the spherical wrist, a discriminant method without solving inverse kinematics equations is proposed for solving the problem whether the robot end-effector can reach the expected position and orientation. Some geometric discrimination conditions are created. Thanks to these geometric discriminant conditions, the visualization of the discriminant result in the virtual environment created in Qt and Ogre3D can be achieved.